Penatalaksanaan Epulis Fibromatosa dengan Electrosurgery (Laporan Kasus) - Trijani Suwandi (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
Background : Epulis is a tumor-like enlargement of the gingiva originating from periodontal connective tissue, which is caused by chronic irritation. Epulis that occurs on the upper anterior teeth will interfere with the aesthetics and function of the lips and reduce self-confidence, thus treatment is deemed necessary. Objective : To evaluate the results of fibromatous epulis treatment using electrosurgery. Case report and management : A 25 year old woman came to the practice with complaints of enlarged gums in the upper front area since 6 months ago. The gum was painful when biting food, and bleed easily during tooth cleaning and brushing. Epulis Fibromatosa treatment was initiated with plaque control, scaling and application metronidazole gel. One week later, the epulis was excised with electrosurgery under local anesthesia. In one week evaluation, the patient had no pain or swelling. Clinical examination showed no residual epulis, marginal gingiva 21 was slightly reddish, and the healing process was going well. The results of the pathology examination showed that the surface covered by stratified squamous epithelium, areas appear erosive and ulcerative, also known as chronic inflammation and no malignancy is found, therefore the diagnosis is Fibromatous Epulis. Patient was instructed to maintain oral health and avoid using toothpicks and are advised for orthodontic treatment. Conclusion : The treatment of Epulis Fibromatosa shows good results with electrosurgery